Protection of Juvenile Delinquents’ Rights Especially in India: Examining the Indian Juvenile Justice System and the Rights of Juvenile Delinquents (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The selection of this subject for in-depth investigation was motivated by the desire to raisequestions about the research into India's Juvenile Justice System. This article provides the context withinwhich the specific decisions on children's rights may be made. Juvenile delinquency served as theinspiration for the creation of the juvenile justice system. Juvenile delinquency is a serious issue intoday's society and a vital factor in determining the status quo. Additionally, most studies show an upwardtrend in adolescent criminality in the last several years. In this article, we explain the protections andrights provided by Indian law, as well as the gaps in India's juvenile justice system.